A Quantitative Pharmacology Model of Exosome-Mediated Drug Efflux and Perturbation-Induced Synergy - Jin Wang; Bertrand Z. Yeung; M. Guillaume Wientjes; Minjian Cui; Cody J. Peer; Ze Lu; William D. Figg; Sukyung Woo; Jessie L.-S. Au (MDPI AG, 2021)
Exosomes, naturally occurring vesicles secreted by cells, are undergoing development as drug carriers. We used experimental and computational studies to investigate the kinetics of intracellular exosome processing and exosome-mediated drug efflux and the effects of exosome inhibition. The experiments used four human-breast or ovarian cancer cells, a cytotoxic drug paclitaxel (PTX), two exosome inhibitors (omeprazole (OME), which inhibits exosome release, and GW4869 (GW), which inhibits synthesis of sphingolipid ceramide required for exosome formation), LC-MS/MS analysis of PTX levels in exosomes, and confocal microscopic study of endocytic transport (monitored using fluorescent nanoparticles and endocytic organelle markers). In all four cells, exosome production was enhanced by PTX but diminished by OME or GW (p < 0.05); the PTX enhancement was completely reversed by OME or GW. Co-treatment with OME or GW simultaneously reduced PTX amount in exosomes and increased PTX amount and cytotoxicity in exosome-donor cells (corresponding to >2-fold synergy as indicated by curve shift and uncertainty envelope analyses). This synergy is consistent with the previous reports that OME co-administration significantly enhances the taxane activity in tumor-bearing mice and in patients with triple negative metastatic breast cancer. The experimental results were used to develop a quantitative pharmacology model; model simulations revealed the different effects of the two exosome inhibitors on intracellular PTX processing and subcellular distribution.